Development of Interest and Role of Choice During Sequential Knowledge Acquisition - Greta M. Fastrich; Kou Murayama (SAGE Publishing, 2020)
Interest is an important motivational element for learning in the school environment. However, little research has directly addressed how interest changes over time as knowledge accumulates. To gain a better understanding of how knowledge acquisition influences intraindividual change of interest, we developed a novel paradigm in which participants gain step-by-step information about lesser known countries. After reading each piece of information, participants rated their interest in the country. Growth-curve modelling showed that interest grows during knowledge acquisition until it eventually stalls and starts to decline. We also found that the opportunity to choose information boosted the growth in interest and delayed its decline. Further analysis revealed that people disengaged from a topic (i.e., stopped accessing information about a particular country) when their interest started to decrease.